2019
DOI: 10.1002/jnm.2576
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐mW 3.9‐dB NF transformer‐based V‐band low‐noise amplifier in 65‐nm CMOS

Abstract: A V-band low-noise amplifier (LNA) employing a Gm-boosting technique is presented in this paper. With the transformers, which are applied between the adjacent stages, the transconductances of the following transistors are boosted. Thus, the gain of the circuit is effectively enhanced. The noise figure (NF) is also decreased with the technique. Utilizing a commercial 65-nm CMOS technology, the LNA is demonstrated. The measurement results show that the LNA achieves a maximum gain of 17.4 dB at 57.1 GHz with 10.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Both applications require compact and lowpower front-ends, usually incorporating a low-noise amplifier (LNA) in the receiver. While transmission-line-based LNA designs are more commonly used in the V-band [6][7][8] due to faster design times, lumped matching can reduce the chip size significantly and transformers can additionally improve performance [9][10][11][12][13][14]. For these it is important to have accurate design equations to accelerate the design phase.…”
mentioning
confidence: 99%
“…Both applications require compact and lowpower front-ends, usually incorporating a low-noise amplifier (LNA) in the receiver. While transmission-line-based LNA designs are more commonly used in the V-band [6][7][8] due to faster design times, lumped matching can reduce the chip size significantly and transformers can additionally improve performance [9][10][11][12][13][14]. For these it is important to have accurate design equations to accelerate the design phase.…”
mentioning
confidence: 99%
“…A different group by Zhang et al 24 reported a balun design algorithm based on compensation matching capacitors and their active S parameters. Using CMOS technology, Chen et al 25 designed a millimeter-wave upconversion mixer by using a two-path transconductance stage and Yu et al 26 reported a linear V-band low-noise amplifier by employing a Gm-boosting technique using full-wave high-frequency structure simulator. Other technologies like GaAs MMIC, hybrid integrated circuits, and electric vacuum devices are also presented by Li et al, 27 Yang et al, 28 and Wang et al, 29 respectively.…”
mentioning
confidence: 99%